2000
DOI: 10.1111/j.1741-3737.2000.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Successful Outcomes Among Preschool Children Born to Low‐Income Adolescent Mothers

Abstract: ࡗ Factors Related to Successful Outcomes AmongPreschool Children Born to Low-Income Adolescent MothersThe purpose of this study was to describe how the experiences and circumstances of the most successful children born to low-income adolescent mothers differed from the experiences and circumstances of the least successful children over the first 54 months of their lives. Success was defined as scoring in the top quartile for this sample on the Peabody Picture Vocabulary Test-Revised (PPVT-R) when the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 20 publications
(21 reference statements)
4
45
0
3
Order By: Relevance
“…This negative relationship found between social support and stress when measured concurrently supports House's (1981) discussion of the beneficial short-term impact of support on stress. This finding corresponds with other research that has revealed the positive effects of support for pregnant and parenting adolescents (e.g., Barrera 1981;Luster et al 2000;Samuels et al 1994;Stevenson et al 1999). Therefore, efforts to build support systems for pregnant and parenting adolescents appear to be good ways to offset the potential stress associated with parenthood.…”
Section: Discussionsupporting
confidence: 90%
“…This negative relationship found between social support and stress when measured concurrently supports House's (1981) discussion of the beneficial short-term impact of support on stress. This finding corresponds with other research that has revealed the positive effects of support for pregnant and parenting adolescents (e.g., Barrera 1981;Luster et al 2000;Samuels et al 1994;Stevenson et al 1999). Therefore, efforts to build support systems for pregnant and parenting adolescents appear to be good ways to offset the potential stress associated with parenthood.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, "the PPVT-R measures an individual's receptive (hearing) vocabulary for Standard American English and provides, at the same time, a quick estimate of verbal ability and scholastic aptitude" (Dunn & Dunn 1981:2). The PPVT-R has been used extensively in studies linking child development to a variety of circumstances surrounding birth, such as mother's age, pregnancy wantedness, and poverty (Geronimus, Korenman & Hillemeir 1994;Guo & Harris 2000;Joyce, Kaestner & Korenman 2000;Luster et al 2000). Interviewers administer the test by saying a word and asking the child to point to the one picture (out of four) that best portrays the meaning of the word.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is necessary to assess the relevance of intergenerational risk to the language development of children of adolescent mothers. Luster, Bates, Fitzgerald, Vandenbelt, and Key (2000) found that the education level of the offspring's maternal grandmother was related to performance in language development at 54 months of age. Similarly, Chase-Lansdale, Brooks-Gunn, and Paikoff (1992) identified that adolescent mothers who were most successful in navigating parenthood were those adolescents whose mothers had higher levels of education and were less likely to depend on public assistance, suggesting that the resources of the family of origin were important to the success of young mothers' transition to adulthood.…”
Section: Introduction: Early Language and Emerging Literacymentioning
confidence: 99%